WHICH SYRUP FLAVOR PEDIATRIC POPULATION PREFERS THE MOST? - PANACHIYIL, GEORGE MATHEW; BABU, TIRIN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: To find out syrup flavor preferences among pediatric patients. Methods: This prospective survey included 350 pediatric patients in a multispecialty hospital and was conducted for over four months. The patients filled a pro forma with a questionnaire regarding the syrup flavor preferences details among four drug categories. If the patients were unable to fill the questionnaire, the parents were asked to fill the same. Results: In our survey, the first preference of the syrup flavors by male gender from all four drug categories were banana-vanilla, orange, lime, and orange-lemon flavors. Whereas, the same in the female gender were the following: Strawberry, grape, banana-pineapple, and strawberry-lemon flavors. Conclusion: The creation of an acceptable syrup taste using flavors should be taken into account by the healthcare professionals before prescribing it to the children.